Canadian French Translation and Validation of the Neck Dissection Impairment Index : A Quality of Life Measure for the Surgical Oncology Population - Khoury, Michel; Guertin, William; Hao, Cameo; Saltychev, Mikhail; Ayad, Tareck; Bissada, Eric; Christopoulos, Apostolos; Moubayed, Sami; Olivier, Marie-Jo; Chepeha, Douglas; Lai, Stephen Y.; Maniakas, Anastasios (Springer Nature, 2025)
Background: Neck dissections (ND) are a routine procedure in head and neck oncology. Given the postoperative functional impact that some patients experience, it is imperative to identify and track quality of life (QoL) symptomatology to tailor each patient's therapeutic needs. To date, there is no validated French-Canadian questionnaire for this patient-population. We therefore sought to translate and validate the Neck Dissection Impairment Index (NDII) in Canadian French.
Methods: A 3-phased approach was used. Phase 1: The NDII was translated from English to Canadian French using a "forward and backward" translational technique following international guidelines. Phase 2: A cognitive debriefing session was held with 10 Canadian French-speaking otolaryngology patients to evaluate understandability and acceptability. Phase 3: The final version was administered prospectively to 30 patients with prior history of ND and 30 control patients. These patients were asked to complete the questionnaire 2 weeks after their first response. Test-retest reliability was calculated with Spearman's correlation. Internal consistency was elicited using Cronbach's alpha.
Results: NDII was successfully translated and validated to Canadian French. Cronbach's alpha revealed high internal consistency (0.92, lower 95% confidence limit 0.89). The correlation for test-retest validity were strong or very strong (0.61-0.91).
Conclusion: NDII is an internationally recognized QoL tool for the identification of ND-related impairments. This validated Canadian French version will allow clinicians to adequately assess the surgery-related QoL effect of neck surgery in the French-speaking population, while allowing French institutions to conduct and/or participate in multisite clinical trials requiring the NDII as an outcome measure.
conduct and/or participate in multisite clinical trials requiring the NDII as an outcome measure.